Implementasi Balanced Scorecard sebagai Alat Pengukur Kinerja pada Koperasi Simpan Pinjam ARTA PANCA JAYA di Kabupaten Sidoarjo - Anita Kartika (UNUSA Press, 2016)
This study aims to determine the performance of Credit Unions ARTA PANCA JAYA when measured using the concept of balanced scorecard through four perspectives, namely: financial perspective, customer perspective, internal business process and learning and growth perspective, so it can be used as information for management in assessing company performance. The data used is quantitative and qualitative data. Quantitative data is data that can be measured, including comparative balance sheet, profit/loss and others. While the qualitative data is data that cannot be measured. The purpose of this study was to make a descriptive/picture, describe a systematic, factual and accurate information on the facts, characteristics and relationships between phenomena diselidiki. This study seeks to get an overview of the performance of companies in this regard, namely Credit Unions ARTA PANCA JAYA when viewed from four perspectives of the balanced scorecard. Performance measurement in this study using a score of -1 for the performance of “less”, and 0 for performance “pretty” and one for performance “good”. Total score assessment of performance against Credit Unions ARTA PANCA JAYA is 8, of the total weight of the standard 15. Thus, the average score is 8/15 = 0.53 (situated between 0 to 0.6).Berdasarkan results of performance assessment Credit Unions ARTA PANCA JAYA in 2010 showed that the performance of Credit Unions ARTA PANCA JAYA overall was good.